2015
DOI: 10.5603/piap.2015.0060
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease Associated with Docetaxel in a Patient Treated for Breast Cancer—A Case Report

Abstract: Docetaxel is a semisynthetic cytostatic drug that belongs to the family of taxoids. Docetaxel inhibits normal interphase and mitotic cellular function, causing cell death. Docetaxel is indicated for the treatment of breast, lung and prostate cancers, head and neck cancer and gastric adenocarcinoma. Interstitial pneumonitis is an uncommon side effect of docetaxel. We report a case of docetaxel induced interstitial lung disease (ILD) in a patient with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Among the chemotherapeutics most associated with inducing RP, especially taxanes have been identified, either alone [29] or as part of combined schedules with other agents, as reported by several studies and case reports in the past [18][19][20][29][30][31]. However, our recent and previous findings [11] regarding the absence of clinically relevant RP induced by taxanes are supported by other studies like that of Yu et al [20], who investigated a cohort of 524 breast cancer patients receiving FAC (5-FU, doxorubicin, cyclophosphamide) with or without paclitaxel and subsequent RT.…”
Section: Discussionmentioning
confidence: 99%
“…Among the chemotherapeutics most associated with inducing RP, especially taxanes have been identified, either alone [29] or as part of combined schedules with other agents, as reported by several studies and case reports in the past [18][19][20][29][30][31]. However, our recent and previous findings [11] regarding the absence of clinically relevant RP induced by taxanes are supported by other studies like that of Yu et al [20], who investigated a cohort of 524 breast cancer patients receiving FAC (5-FU, doxorubicin, cyclophosphamide) with or without paclitaxel and subsequent RT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of lung injury is debatable, the most common pattern of lung injury described is that of hypersensitivity pneumonitis. [9] Some studies have reported that bronchoscopy and bronchoalveolar lavage may give some evidence to support the diagnosis of drug-induced pneumonitis based on lymphocytic alveolitis, leukocytosis, and a low CD4/CD8 ratio. [4] Transbronchial lung biopsy may show nonspecific alveolar and interstitial edema with mononuclear cellular infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, docetaxel is classified as a tetracyclic diterpenoid and taxoid antineoplastic agent, which is utilized in the medical field for the management of various forms of cancer. These include locally advanced or metastatic breast cancer, metastatic prostate cancer, gastric adenocarcinoma, and head and neck cancer (Pankowska-Supryn et al, 2015). The pharmaceutical compound known as alitretinoin, which is derived from vitamin A, is utilized in the treatment of Kaposi's sarcoma (Bodsworth et al, 2001).…”
Section: Introductionmentioning
confidence: 99%